Produção e caracterização de anticorpos monoclonais contra uma cepa do herpesvírus bovino tipo 1 defectiva no gene da glicoproteína C - Winkelmann, Evandro Reinoldo (2006)
Bovine herpesvirus type 1 (BoHV-1) is an important pathogen of cattle and causes significant economic losses to livestock industry. Monoclonal antibodies (mAbs) represent useful tools for diagnostic and research purposes. Most mAbs produced against BoHV-1 are directed to glycoprotein gC (gC), an abundant and immunodominant envelope antigen. In the present study, antigens of a BoHV-1 strain defective in the gene coding for glycoprotein C was used to immunize BALB/c mice to produce mAbs with other protein specificities. After fusion and selection of 54 hybridomas resistant to the selective medium HAT, three hybridomas secreting mAbs directed to BoHV-1 antigens were obtained (1F1, 2H4, 4D7). The mAbs belong to the IgG2a isotype and reacted in an indirect fluorescent antibody assay (IFA) and indirect immunoperoxidase staining (IPX) of BoHV-1-infected cells at dilutions up to 1:640 (culture supernatant) and 1:20,000 (ascitic fluid). The three mAbs tested reacted with 14 isolates of respiratory and/or genital disease and with 17 isolates of neurological disease and showed variable level of neutralizing activity against the most of these isolates. The protein specificity of the mAbs could not be determined, because none of them reacted with viral proteins in western immunoblot. On the other hand, the three mAbs reacted in IFA with viral antigens of BoHV-1 and BoHV-5 mutant strains defective on gC, gE, gI and US9 genes, demonstrating that they are directed against other viral antigens. Because the high reaction titer and the wide range of reactivity, these mAbs have potential use in diagnostics techniques. Also, these mAbs may be useful to map conserved neutralizing epitopes in the envelope glycoproteins